Fillers, methods for their preparation and use, and gas phase oxidation processes
Patent Information
- Application Number
- CN202210742772.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-06-28
AI Technical Summary
[0003]本发明所要解决的技术问题之一是现有技术填料蓄热能力较差的问题,提供一种填料,该填料蓄热能力优异;该填料用于选择性氧化反应可以提高反应装置的蓄热能力,降低装置能耗,延长催化剂使用寿命
[0014]本发明提供的填料蓄热能力优异,所述填料的制备方法具有低成本、简单的优点。本发明所述的填料用于选择性氧化反应,可以提高反应装置的蓄热能力,降低装置能耗,延长催化剂使用寿命,同时具有提高目标氧化产物收率优点。
Smart Images

Figure BDA0003718620520000091 
Figure BDA0003718620520000101 
Figure BDA0003718620520000111
Abstract
Description
Technical Field
[0001] This invention belongs to the field of reactor packing technology, specifically relating to a packing material, its preparation method and application, and a gas-phase oxidation method. Background Technology
[0002] Packing materials are commonly used in fixed-bed reactors. Placed at the bottom and top of the reactor, and mixed with the catalyst in a specific ratio, they support the catalyst, preheat the reaction substrate, and transfer heat, playing a crucial role in energy saving and long-term stable operation of the unit. Current technologies primarily use inert ceramic balls or Raschig rings, which are mostly general-purpose products and not specifically optimized for highly exothermic reactions. Their heat storage capacity is poor, failing to meet the requirements for energy saving and extended catalyst lifespan. Summary of the Invention
[0003] One of the technical problems to be solved by the present invention is that the heat storage capacity of existing packing materials is poor. The present invention provides a packing material with excellent heat storage capacity. When used in selective oxidation reactions, the packing material can improve the heat storage capacity of the reaction device, reduce the energy consumption of the device, and extend the service life of the catalyst.
[0004] The second technical problem to be solved by the present invention is that the existing preparation methods are difficult to produce packing with high heat storage capacity. The present invention provides a low-cost and simple method for preparing packing that can be used in fixed-bed reactors.
[0005] To achieve the objectives of this invention, a first aspect of this invention provides a filler containing one or more oxides of silicon and / or aluminum and optionally a metal, wherein the filler has a hollow sphere structure with an outer diameter of 20-60 μm and a wall thickness of 2-30 μm.
[0006] A second aspect of the present invention provides a method for preparing the packing material described herein, the method comprising:
[0007] (1) A mixture containing silicon and / or aluminum, as well as optional metals and water-soluble solid organic acids, is mixed to form an aqueous mixture with a solid content of less than 55% by weight;
[0008] (2) The aqueous mixture is spray-dried to obtain the precursor;
[0009] (3) The precursor is first calcined to obtain powder;
[0010] (4) Mix the powder, binder and optional other additives into a mold, and then perform a second firing.
[0011] A third aspect of the present invention provides the application of the filler described herein in a selective oxidation reaction.
[0012] A fourth aspect of the present invention provides a gas-phase oxidation method, the method comprising:
[0013] The packing material and oxidation catalyst are loaded into the reactor, and the raw material gas, oxygen-containing gas, optionally inert gas and / or water vapor are introduced into the reactor to contact with the oxidation catalyst to obtain oxidation products. The packing material contains the packing material described in this invention.
[0014] The packing material provided by this invention has excellent heat storage capacity, and the preparation method of the packing material has the advantages of low cost and simplicity. The packing material of this invention, when used in selective oxidation reactions, can improve the heat storage capacity of the reaction device, reduce energy consumption, extend catalyst lifespan, and simultaneously increase the yield of the target oxidation product. Detailed Implementation
[0015] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0016] The first aspect of this invention provides a packing material containing one or more oxides of silicon and / or aluminum and optionally a metal. The packing material has a hollow spherical structure with an outer diameter of 20-60 μm and a wall thickness of 2-30 μm. The packing material provided by this invention has excellent heat storage capacity.
[0017] According to a preferred embodiment of the present invention, the outer diameter of the hollow spheres is 30-45 μm, which is beneficial to improving the heat storage capacity of the packing.
[0018] According to a preferred embodiment of the present invention, the wall thickness of the hollow spheres is 7-20 μm, which is beneficial to improving the heat storage capacity of the packing.
[0019] According to a preferred embodiment of the present invention, the crushing strength of the packing is 100-1000N.
[0020] According to a preferred embodiment of the present invention, the wear rate of the packing is 0.1-5%.
[0021] According to a preferred embodiment of the present invention, the particle size of the filler is 3.5-8 mm.
[0022] According to a preferred embodiment of the present invention, the packing material is spherical and / or Raschig ring shaped.
[0023] According to a preferred embodiment of the present invention, the specific surface area of the packing is 5-150 m².2 / g.
[0024] According to a preferred embodiment of the present invention, the pore volume of the packing is 0.01-0.6 cm³. 3 / g.
[0025] In this invention, there is no particular limitation on the metal element, which can be a metal element commonly used in the art. According to a preferred embodiment of the invention, the metal element is selected from one or more of group IVB metal elements and rare earth metal elements, preferably selected from one or more of Ti, Zr, Ce, La, Pr and Nd; this is beneficial to improving the heat storage capacity of the filler.
[0026] According to a preferred embodiment of the present invention, the filler contains oxides of at least two of silicon and / or aluminum and optionally metals; this is beneficial for improving the heat storage capacity of the filler.
[0027] The fillers having the aforementioned features of this invention can all achieve the objectives of this invention, and there is no particular limitation on their preparation methods. According to a preferred embodiment of this invention, this invention provides a method for preparing the fillers of this invention, the method comprising:
[0028] (1) A mixture containing silicon and / or aluminum, as well as optional metals and water-soluble solid organic acids, is mixed to form an aqueous mixture with a solid content of less than 55% by weight;
[0029] (2) The aqueous mixture is spray-dried to obtain the precursor;
[0030] (3) The precursor is first calcined to obtain powder;
[0031] (4) The powder, binder, and optional other additives are mixed and shaped, and then subjected to a second calcination. In the preparation method of the present invention, the solid content of the aqueous mixture is controlled to be below 55% by weight and the spray drying method of the present invention is used to achieve the hollow spherical structure of the filler. The preparation method of the filler provided by the present invention has the advantages of low cost and simplicity, and the prepared filler has excellent heat storage capacity.
[0032] According to a preferred embodiment of the present invention, at least two of the following substances—silicon-containing materials and / or aluminum-containing materials and metallic materials—are used to form an aqueous mixture with a solid content of less than 45% by weight; this is beneficial for improving the heat storage capacity of the packing.
[0033] According to a preferred embodiment of the present invention, the content of water-soluble solid organic acid is 1-10%, preferably 5-8%, based on the total weight of the aqueous mixture.
[0034] In this invention, there is no particular limitation on the type of silicon-containing material, which can be a conventional silicon-containing material in the art. Preferably, the silicon-containing material is selected from one or more of silica sol, silica, silica gel, silica glass and silicon-containing molecular sieve.
[0035] In this invention, there is no particular limitation on the type of aluminum-containing material, which can be any aluminum-containing material conventional in the art. Preferably, the aluminum-containing material is selected from one or more of aluminum sol, aluminum nitrate, aluminum hydroxide, aluminum oxide and aluminum-containing molecular sieves.
[0036] In this invention, there is no particular limitation on the type of metallic substance, which can be a conventional metallic substance in the art. Preferably, the metallic substance is selected from soluble metal compounds.
[0037] In this invention, there is no particular limitation on the type of adhesive, which can be a conventional adhesive in the art. Preferably, the adhesive is selected from at least one of water, nitric acid solution, hydrochloric acid solution, silica sol, aluminum sol and titanium sol.
[0038] In this invention, the water-soluble solid organic acid is a conventional water-soluble solid organic acid in the art. Preferably, the water-soluble solid organic acid is selected from one or more of oxalic acid, citric acid, tartaric acid and malic acid, preferably a mixture of citric acid and tartaric acid, and more preferably a mass ratio of citric acid to tartaric acid of 1:0.5-2.
[0039] According to the present invention, other additives conventional in the art can be added to the powder as raw materials for the filler. According to a preferred embodiment of the present invention, the additive is selected from lubricants, and preferably, the lubricant is selected from at least one of stearic acid, graphite and magnesium stearate.
[0040] According to a preferred embodiment of the present invention, the molding method is one of extrusion molding, ball rolling molding, or sheet forming.
[0041] According to a preferred embodiment of the present invention, in step (1), the solid content of the aqueous mixture is 10wt%-40wt%, preferably 15-30wt%, which is beneficial to improving the heat storage capacity of the packing.
[0042] According to a preferred embodiment of the present invention, in step (1), the mixing conditions include: a temperature of 20-100°C and a stirring time of 0.1-48h, preferably 2-12h.
[0043] According to a preferred embodiment of the present invention, in step (2), the conditions for spray drying include: the spray dryer speed is 15000-35000 rpm / min, preferably 20000-25000 rpm / min; the outlet temperature is 100-200℃, preferably 130-150℃; which is beneficial to improving the heat storage capacity of the packing.
[0044] According to a preferred embodiment of the present invention, the conditions for the first calcination include: the temperature of the first calcination is 300-500°C; the calcination atmosphere is air and / or an inert atmosphere; the inert atmosphere is preferably nitrogen and / or an inert gas, wherein the inert gas is, for example but not limited to, He, Ne and / or Ar.
[0045] According to the present invention, the roasting time is reasonably adjusted according to the temperature of the first roasting, preferably, the roasting time is 3 to 10 hours.
[0046] According to a preferred embodiment of the present invention, the conditions for the second calcination include: a second calcination temperature of 800-1500°C; and a calcination atmosphere of air and / or an inert atmosphere. The inert atmosphere is preferably nitrogen and / or an inert gas, wherein the inert gas is, for example but not limited to, He, Ne, and / or Ar.
[0047] According to the present invention, the roasting time is reasonably adjusted according to the temperature of the second roasting, preferably, the roasting time is 3 to 10 hours.
[0048] A third aspect of the present invention provides the application of the filler described herein in a selective oxidation reaction.
[0049] According to a preferred embodiment of the present invention, the filler described herein is applied in the production process of selective oxidation of propylene to acrolein, selective oxidation of acrolein to acrylic acid, selective oxidation of isobutylene to methacrolein, or selective oxidation of methacrolein to methacrylic acid.
[0050] A fourth aspect of the present invention provides a gas-phase oxidation method, the method comprising:
[0051] A packing material and an oxidation catalyst are loaded into a reactor. A feed gas, containing oxygen, optionally an inert gas, and / or water vapor, is introduced into the reactor to contact the oxidation catalyst and obtain oxidation products. The packing material contains the packing material described in this invention. The packing material described in this invention is used for selective oxidation reactions, which can improve the heat storage capacity of the reaction device, reduce energy consumption, extend catalyst life, and simultaneously increase the yield of the target oxidation product.
[0052] According to a preferred embodiment of the present invention, the contact conditions include: a temperature of 240-450°C, with molten salt as the heat dissipation source, and the contact temperature can be referred to as the salt temperature.
[0053] In this invention, the gas-phase oxidation reaction is a selective oxidation reaction. According to a preferred embodiment of the invention, the raw material gas is one or more of propylene, acrolein, isobutylene, and methacrolein.
[0054] According to a preferred embodiment of the present invention, the oxidation product is one or more of acrolein, acrylic acid, methacrolein, and methacrylic acid.
[0055] According to a preferred embodiment of the present invention, the volume concentration of the raw gas is 1-15%.
[0056] According to a preferred embodiment of the present invention, when the feed gas is propylene and / or isobutylene, the volume concentration of the feed gas is 3-15%.
[0057] According to a preferred embodiment of the present invention, when the feed gas is acrolein and / or methacrolein, the volume concentration of the feed gas is 1%-10%.
[0058] According to a preferred embodiment of the present invention, the linear velocity of the raw gas is in the range of 0.5-10 m / s.
[0059] According to a preferred embodiment of the present invention, the reactor is a tubular reactor for heat dissipation by molten salt and / or heat transfer oil, with a tube diameter of 2-5 cm.
[0060] According to a preferred embodiment of the present invention, the total packing height of the oxidation catalyst and the packing material is 2-6 meters.
[0061] According to a preferred embodiment of the present invention, the catalyst loading concentration in the reactor is gradually increased in stages according to the feeding direction, preferably in 2-10 stages, more preferably in 2 stages, and the concentration difference of the catalyst between two adjacent stages is 5-50%, more preferably 10-30%, and more preferably 12%-28%.
[0062] The concentration of the catalyst refers to the weight concentration of the catalyst in each section relative to the total weight of the catalyst and packing material.
[0063] In this invention, the catalyst is not particularly limited and can be any conventional catalyst in the art.
[0064] The present invention will be described in detail below through embodiments.
[0065] In the following embodiments, the specific surface area and pore volume of the packing were tested using a Tristar II nitrogen adsorption-desorption instrument from Micron Technology, Inc., USA, and the analytical methods were BET and BJH methods.
[0066] The wear test method is based on the People's Republic of China Chemical Industry Standard HG / T 2976-1999.
[0067] Example 1
[0068] (1) Dissolve 375g of aluminum nitrate (Al(NO3)3·9H2O) and 42.9g of zirconium nitrate (Zr(NO3)4·5H2O) in 100g of deionized water, then add 24g of citric acid, and stir at 60℃ for 2h to form a water-containing mixture with a solid content of 50% by weight.
[0069] (2) The aqueous mixture is spray-dried to obtain the precursor. The spray dryer speed is 20000 rpm / min and the outlet temperature is 120℃.
[0070] (3) The precursor is placed in an air atmosphere for a first calcination to obtain powder; the temperature of the first calcination is 500℃ and the calcination time is 12h;
[0071] (4) 500g of precursor, 50g of dilute nitric acid (2wt%), and 10g of graphite were kneaded together and then placed in an air atmosphere for a second calcination. The second calcination temperature was 1000℃ and the calcination time was 10h to prepare the filler. The test results are shown in Table 1.
[0072] Example 2
[0073] (1) Dissolve 375g of aluminum nitrate (Al(NO3)3·9H2O) and 42.9g of zirconium nitrate (Zr(NO3)4·5H2O) in 640g of deionized water, then add 24g of citric acid, and stir at 60°C for 2h to form a water-containing mixture with a solid content of 25% by weight.
[0074] (2) The aqueous mixture is spray-dried to obtain the precursor. The spray dryer speed is 20000 rpm / min and the outlet temperature is 120℃.
[0075] (3) The precursor is placed in an air atmosphere for a first calcination to obtain powder; the temperature of the first calcination is 500℃ and the calcination time is 12h;
[0076] (4) 500g of precursor, 50g of dilute nitric acid (2wt%), and 10g of graphite were kneaded together and then placed in an air atmosphere for a second calcination. The second calcination temperature was 1000℃ and the calcination time was 10h to prepare the filler. The test results are shown in Table 1.
[0077] Example 3
[0078] (1) Dissolve 375g of aluminum nitrate (Al(NO3)3·9H2O) and 42.9g of zirconium nitrate (Zr(NO3)4·5H2O) in 2268g of deionized water, then add 24g of citric acid, and stir at 60°C for 2h to form a water-containing mixture with a solid content of 10% by weight.
[0079] (2) The aqueous mixture is spray-dried to obtain the precursor. The spray dryer speed is 20000 rpm / min and the outlet temperature is 120℃.
[0080] (3) The precursor is placed in an air atmosphere for a first calcination to obtain powder; the temperature of the first calcination is 500℃ and the calcination time is 12h;
[0081] (4) 500g of precursor, 50g of dilute nitric acid (2wt%), and 10g of graphite were kneaded together and then placed in an air atmosphere for a second calcination. The second calcination temperature was 1000℃ and the calcination time was 10h to prepare the filler. The test results are shown in Table 1.
[0082] Example 4
[0083] Compared with Example 2, the difference is that the aqueous mixture was spray-dried to obtain the precursor, and the spray dryer speed was 30,000 rpm; the other conditions were the same as in Example 1. The test results are shown in Table 1.
[0084] Example 5
[0085] Compared with Example 2, the difference is that the aqueous mixture was spray-dried to obtain the precursor, and the spray dryer speed was 15000 rpm; the other conditions were the same as in Example 1. The test results are shown in Table 1.
[0086] Example 6
[0087] Compared with Example 2, the difference is that the aqueous mixture is spray-dried to obtain the precursor at an outlet temperature of 150°C; the other conditions are the same as in Example 1. The test results are shown in Table 1.
[0088] Example 7
[0089] Compared with Example 2, the difference is that the aqueous mixture is spray-dried to obtain the precursor, and the outlet temperature is 180°C; the other conditions are the same as in Example 1. The test results are shown in Table 1.
[0090] Comparative Example 1
[0091] The difference from Example 2 is that citric acid was not added in step (1). The test results are shown in Table 1.
[0092] Table 1
[0093]
[0094]
[0095] Examples 8-14
[0096] The fillers from Examples 1-7 were used in the oxidation of propylene to acrolein under the following reaction conditions:
[0097] The reactant propylene was passed into a fixed-bed reactor packed with catalyst. The reaction product was absorbed with dilute acid at 0°C, and then analyzed by gas chromatography. During the analysis, the carbon balance was calculated, and data with a carbon balance of 95%–105% were selected as valid data. The reaction conditions were as follows:
[0098] Reactor: Fixed-bed reactor, inner diameter 25.4 mm, length 1500 mm;
[0099] According to the feeding direction, fill F1 and F2, two sections, and the specific filling ratio is shown in Table 2;
[0100] Raw material volume ratio: propylene: air: water vapor = 1:7.6:1.7;
[0101] Propylene volumetric hourly space velocity: 110 mL·h -1 ·g -1 ;
[0102] The linear velocity of the reaction gas flow is 1 m / s.
[0103] Examples 15-17
[0104] Compared with Example 13, the difference lies in the filling ratio; all other conditions are the same as in Example 13. The test results are shown in Table 2.
[0105] Comparative Example 2
[0106] Commercially available Al2O3 spheres, 5 mm in diameter, were used, with all other conditions the same as in Example 13. The test results are shown in Table 2.
[0107] Comparative Example 3
[0108] The packing material was prepared in Comparative Example 1 and tested according to the reaction conditions of Examples 8-14. The test results are shown in Table 2.
[0109] Table 2
[0110]
[0111]
[0112] As shown in Table 2, Examples 8-17 are packings prepared using the technical solution of the present invention. Compared with Comparative Example 1, the reactor salt temperature decreased significantly, indicating that the packings described in the present invention can improve the heat storage capacity of the reaction device and reduce the energy consumption of the device.
[0113] Example 18
[0114] Unlike Example 2, the solid content of the aqueous mixture was 52%, and the other preparation conditions were the same as in Example 2. The evaluation conditions were the same as in Example 13. The specific results are shown in Table 3.
[0115] Example 19
[0116] Unlike Example 2, the citric acid content was 1% by weight, and the other preparation conditions were the same as in Example 2. The evaluation conditions were the same as in Example 13. The specific results are shown in Table 3.
[0117] Example 20
[0118] Unlike Example 2, 30.0g of titanium nitrate was used instead of zirconium nitrate. The other preparation conditions were the same as in Example 2, and the evaluation conditions were the same as in Example 13. The specific results are shown in Table 3.
[0119] Example 21
[0120] Unlike Example 2, 43.42g of cerium nitrate hexahydrate was used instead of zirconium nitrate. The other preparation conditions were the same as in Example 2, and the evaluation conditions were the same as in Example 13. The specific results are shown in Table 3.
[0121] Example 22
[0122] Unlike Example 2, the water-soluble solid acid was a mixture of citric acid and tartaric acid (mass ratio 1:1). The other preparation conditions were the same as in Example 2, and the evaluation conditions were the same as in Example 13. The specific results are shown in Table 3.
[0123] Table 3
[0124] Example 18 315 97% Example 19 320 98% Example 20 305 99% Example 21 304 99% Example 22 305 99%
[0125] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A gas-phase oxidation method, characterized in that, The method includes: loading packing material and an oxidation catalyst into a reactor; introducing feed gas, oxygen-containing gas, and water vapor into the reactor to contact the oxidation catalyst to obtain oxidation products; gradually increasing the catalyst concentration in the reactor according to the feed direction; filling two sections of catalyst in the reactor with a concentration difference of 12-28%; the catalyst concentration refers to the weight concentration of catalyst in each section relative to the total weight of catalyst and packing material; the packing material is a hollow spherical structure with an outer diameter of 30-45 μm and a wall thickness of 7-20 μm; the wear rate of the packing material is 0.1-5%; the particle size of the packing material is 3.5-8 mm; the shape of the packing material is a Raschig ring; and the specific surface area of the packing material is 5-150 m². 2 / g; the pore volume of the packing is 0.01-0.6cm³. 3 / g; The methods for preparing fillers include: (1) A mixture containing aluminum, metal, and water-soluble solid organic acid is mixed to form an aqueous mixture with a solid content of less than 55% by weight; the metal element in the metal is selected from one or more of Ti, Zr, Ce, La, Pr and Nd; (2) The aqueous mixture is spray-dried to obtain a precursor; (3) The precursor is subjected to a first calcination to obtain powder; (4) Mix the powder, binder and additives into a mold, and then perform a second firing.
2. The method according to claim 1, wherein, The content of water-soluble solid organic acids is 1-10% based on the total weight of the aqueous mixture; and / or The aluminum-containing material is selected from one or more of aluminum sol, aluminum nitrate, aluminum hydroxide, alumina, and aluminum-containing molecular sieves; and / or The metallic substance is selected from soluble metal compounds; and / or The water-soluble solid organic acid is selected from one or more of oxalic acid, citric acid, tartaric acid, and malic acid; and / or The binder is selected from at least one of water, nitric acid solution, hydrochloric acid solution, silica sol, aluminum sol, and titanium sol; and / or The additive is selected from lubricants; and / or The forming method is one of extrusion molding, ball rolling molding, or sheet forming.
3. The method according to claim 2, wherein, The content of water-soluble solid organic acids is 5-8% based on the total weight of the aqueous mixture; and / or The water-soluble solid organic acid is a mixture of citric acid and tartaric acid, with a mass ratio of citric acid to tartaric acid of 1:0.5-2; and / or The lubricant is selected from at least one of stearic acid, graphite, and magnesium stearate.
4. The method according to claim 1, wherein, In step (1), The solid content of the aqueous mixture is 10wt%-40wt%, and / or Mixing conditions include: a temperature of 20-100℃ and a stirring time of 0.1-48 h; and / or In step (2), The conditions for spray drying include: a spray dryer speed of 15,000-35,000 rpm and an outlet temperature of 100-200℃; and / or The conditions for the first roasting include: the temperature of the first roasting is 300-500℃; the roasting atmosphere is air and / or an inert atmosphere; The conditions for the second calcination include: the temperature of the second calcination is 800-1500℃; and the calcination atmosphere is air and / or an inert atmosphere.
5. The method according to claim 1, wherein, Contact conditions include: a temperature of 240-450℃; and / or The feed gas is one or more of propylene, acrolein, isobutylene, and methacrolein; and / or The oxidation product is one or more of acrolein, acrylic acid, methacrolein, and methacrylic acid; The linear velocity of the feed gas ranges from 0.5 to 10 m / s.
6. The method according to claim 1, wherein, The reactor is a tubular reactor that dissipates heat using molten salt and / or heat transfer oil, with a tube diameter of 2-5 cm.
Citation Information
Patent Citations
Hollow spherical glass particles
CN112469677A
Coke-oven gas hydrodesulfurization catalyst as well as preparation method and application thereof
CN112742362A
Catalyst for preparing methacrylic acid and preparation method and application thereof
CN113083337A